1983
DOI: 10.1002/ijc.2910320611
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of urinary androgen levels and ovarian cancer

Abstract: The three major urinary androgen metabolites, dehydroepiandrosterone (DHEA), androsterone (ANDRO), and aetiocholanolone (AETIO) were measured in 1,484 volunteer women between 29 and 60 years of age on the island of Guernsey from 1962-1967. Twelve of these women subsequently developed ovarian cancer after a median interval of 130 months and a minimum interval of 19 months. All three androgen levels in these women were lower than those in controls matched for age and menopausal status. The results were most stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…More direct evidence for a role of androgens in the development of ovarian cancer was provided by 2 prospective studies [37,39], both of which showed an increased ovarian cancer risk (though non-significantly in one [39]) among those with elevated prediagnostic serum levels of androstenedione (particularly among pre-menopausal women). Interestingly, urinary androgens levels were shown to be lower in controls compared to cases in an earlier small prospective study conducted in the Island of Guernsey [42]. However, the small size of this study (12 cases) increases the probability that chance played a role in their findings.…”
Section: Androgenscontrasting
confidence: 57%
“…More direct evidence for a role of androgens in the development of ovarian cancer was provided by 2 prospective studies [37,39], both of which showed an increased ovarian cancer risk (though non-significantly in one [39]) among those with elevated prediagnostic serum levels of androstenedione (particularly among pre-menopausal women). Interestingly, urinary androgens levels were shown to be lower in controls compared to cases in an earlier small prospective study conducted in the Island of Guernsey [42]. However, the small size of this study (12 cases) increases the probability that chance played a role in their findings.…”
Section: Androgenscontrasting
confidence: 57%
“…A prospective study published in 1985 assessed the urinary concentrations of DHEA as well as metabolites of testosterone, androsterone, and etiocholanolone, in 1484 women, 12 of whom subsequently developed ovarian cancer and found that the levels of DHEA ( P = 0.007), androsterone ( P = 0.06), and etiocholanolone ( P = 0.33) in ovarian cancer patients were lower than those in control subjects [8]. Another prospective study published in 1995 compared the serum levels of adrenal androgens in 31 patients with ovarian cancer versus 62 control women matched on race, age, and menopausal status, as well as the number of days from the beginning of the last menstrual period (in premenopausal women) and year from the last menstrual period (in postmenopausal women) [9].…”
Section: Role Of Androgens and Ar Signaling In Ovarian Carcinogenesismentioning
confidence: 99%
“…A recognized protective factor is young age at first p r e g n a n~y ,~' ,~~ whereas early menarche and late menopause are associated with increased risk.23-25 Low urinary androgen levels have been observed in women who subsequently developed breast cancer, and the same abnormality was found for cancer of the ovary. 26 Casagrande et aL2' found obesity (defined as at least 20% weight excess for a given height) to be a risk factor for ovarian carcinoma. This conclusion was based on a case-control study of 150 patients with cancer of the ovary, all younger than 50 years of age.…”
Section: Cancer Of the Ovarymentioning
confidence: 99%